Continuous dependence on the parameter of solutions of impulse evolutionary systems - Rogovchenko , Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A theorem on continuous dependence of the solutions of a nonlinear impulse evolution system on a parameter is proved; this theorem can be used as a basis for an averaging principle.